Double Perovskite Ba2LaTaO6 for Ultrafast Fiber Lasers in Anomalous and Normal Net Dispersion Regime - Yiqing Shu; Mingqi An; Penglai Guo; Xun Yuan; Leiming Wu; Zhitao Lin; Weicheng Chen; Xiaohui Li; Jianqing Li (Nanomaterials, 2022)
Double perovskites (DPs) have been attracting attention in an assortment of optoelectronic applications, for they hold advantages such as high quantum efficiency, long carrier migration distance and strong linear and nonlinear absorptions. As specific kinds of perovskites (PVKs), DPs are gifted with orthorhombic crystal structures which provide rich conversion combinations and broaden the space for research and application. However, few works have been reported about DPs in ultrafast photonics applications. In this article, a DP with chemical formula of Ba2LaTaO6 (BLT) was successfully synthesized by high-temperature solid phase method. The microstructures and morphologies were observed, and the linear and nonlinear absorption were characterized. By first using BLT as a novel saturable absorber in both normal and anomalous dispersion region fiber lasers, dual-wavelength soliton and dissipative soliton were successfully operated at C-band. This study affirms BLT’s nonlinear optical properties, lays the foundation for optical research on BLT, and meanwhile provides a meaningful reference for future development of pulsed lasers based on DPs.